Psychological Features of Stress Situation Prevention in Coursants (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article provides information on the psychological mechanisms for the prevention of stressful situations in cadets. At the same time, the main features, causes, and factors of stress resistance prevention are indicated. In particular, the essence of psychological measures to prevent stressful situations in military activities is highlighted.